Security Threats Posed by Contraband Cell Phones in Naivasha Maximum Prison in Kenya: Prison Officers’ Perspectives - Kariuki, John Ngugi; Mwangi, Wokabi; Murenga, Hadija (Advances in Social Sciences Research Journal, 2020)
In the recent past, cell phones have emerged to be among the leading outlawed contemporary contrabands in correctional facilities around the globe. Although official statistics on the number of contraband cell phones globally remains elusive, searches by prison officials project a worrisome trend. At Naivasha Maximum Prison, it is estimated that 30% of the inmates possess one cell phone. Existing studies are more inclined to how phones are smuggled, who smuggle them and their impact on rehabilitation of offenders. Limited studies have been carried out to examine the security threats posed by smuggling and use of cell phones into the prisons. One school of thought argues that cell phones are smuggled into prisons and used by inmates for a good course including communicating with their significant others and for leisure. The other school of thought argues that they are used to commit crimes and thus a source of insecurity to officers, inmates and the members of public. This paper is guided by three specific objectives; to examine security threats prison officers are prone to due to smuggling and use of cell phones at the prison; to examine security threats inmates are prone to due to smuggling and use of cell phones at the prison and finally to examine security threats members of public are prone to due to smuggling and use of cell phones at the prison. The study employed descriptive research design. The unit of analysis was an individual prison officer. A sample size of 182 respondents was drawn from a population of 507 junior prison officers using simple random sampling technique. Primary data was collected through questionnaires. The results of this study indicated that prison officers are prone to physical injuries (38.92%), ambushes during escorts (29.94%) and espionage (20.35%). Inmates were prone to physical attacks (46.78%), electronic fraud (26.28%) and exploitation (21.79%). Members of public were prone to electronic fraud (74.40%) and kidnappings (40.47%). This current study concluded that cell phones in prison facilities pose significant security threats to prison officers, inmates and the members of public. These security threats are therefore of national concern. This study will add to existing body of knowledge on prisons and address policy gaps that exists in controlling cell phones in prison facilities.